Current Issues of Improving the System of Public Procurement of Medicines - Alekseevna, Prodanova Natalia; Ivanovna, Zatsarinnaya Elena; Stepanovna, 3Plaskova Nataliya; Alekseevna, Reshina Galina; Valeryevna, Chumakova Natalya; Albertovna, Mayorova Irina (International Journal of Psychosocial Rehabilitation, 2020)
One of the main objects of state orders in the field of healthcare is medicines. They have a high social significance and have a direct impact on the human body. Despite the existence of a broad legal framework regulating the process of state and municipal procurement, there are many problems in this area at different stages of procurement, which the authors have tried to systematize in this article, as well as to outline measures that would contribute to improving the system of public procurement of medicines in general.